Do as I say not as I do : a critique of G-7 proposals on reforming the multilateral development banks - Kapur, Devesh (UN New YorkUS, 2003)
Addresses the issue of the restructuring of the International Development Association (IDA) with a part of its lending in the form of grants rather than loans. Examines the issues of the harmonization of procedures, policies and overlapping mandates among multilateral development banks (MDBs). Focuses on the issue of the volume of support by MDBs for global public goods (GPGs) and the rankings and priorities among them.